Athanasius' use of the Gospel of John: a rhetorical analysis of Athanasius' Orations against the Arians - Boezelman, Wijnand Adrianus ca. 20./21. Jahrhundert (Gorgias studies in early Christianity and patristics, 2021)
Conceptual framework -- General remarks about the Orations against the Arians -- Analysis of Oration I -- Analysis of Oration II -- Analysis of Oration III.